The calcium-activated slow AHP: cutting through the Gordian knot - Andrade, Rodrigo; Foehring, Robert C.; Tzingounis, Anastasios V. (Frontiers in Cellular Neuroscience, 2012)
The phenomenon known as the slow afterhyperpolarization (sAHP) was originally described more than 30 years ago in pyramidal cells as a slow, Ca2+-dependent afterpotential controlling spike frequency adaptation. Subsequent work showed that similar sAHPs were widely expressed in the brain and were mediated by a Ca2+-activated potassium current that was voltage independent, insensitive to most potassium channel blockers, and strongly modulated by neurotransmitters. However the molecular basis for this current has remained poorly understood. The sAHP was initially imagined to reflect the activation of a potassium channel directly gated by Ca2+ but recent studies have begun to question this idea. The sAHP is distinct from the Ca2+-dependent fast and medium AHPs in that it appears to sense cytoplasmic [Ca2+]i and recent evidence implicates proteins of the neuronal calcium sensor family as diffusible cytoplasmic Ca2+ sensors for the sAHP. Translocation of Ca2+-bound sensor to the plasma membrane would then be an intermediate step between Ca2+ and the sAHP channels. Parallel studies strongly suggest that the sAHP current is carried by different potassium channel types depending on the cell type. Finally, the sAHP current is dependent on membrane PtdIns(4,5)P2 and Ca2+ appears to gate this current by increasing PtdIns(4,5)P2 levels. Because membrane PtdIns(4,5)P2 is essential for the activity of many potassium channels, these finding have led us to hypothesize that the sAHP reflects a transient Ca2+-induced increase in the local availability of PtdIns(4,5)P2 which then activates a variety of potassium channels. If this view is correct, the sAHP current would not represent a unitary ionic current but the embodiment of a generalized potassium channel gating mechanism. This model can potentially explain the cardinal features of the sAHP, including its cellular heterogeneity, slow kinetics, dependence on cytoplasmic [Ca2+], high temperature-dependence, and modulation.